2022
DOI: 10.2337/dc22-1622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intermittent Fasting in People With Insulin-Treated Type 2 Diabetes (INTERFAST-2)—A Randomized Controlled Trial

Abstract: OBJECTIVE To investigate the safety and feasibility of 3 nonconsecutive days of intermittent fasting (IF) per week over 12 weeks in participants with insulin-treated type 2 diabetes. RESEARCH DESIGN AND METHODS Forty-six people were randomized to an IF or control group. Dietary counseling and continuous glucose monitoring was provided. Coprimary end points were the change in HbA1c from baseline to 12 weeks and a composite end… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 17 publications
(21 reference statements)
0
48
2
Order By: Relevance
“…A decline in resting metabolic rate (RMR) is described for most caloric restriction interventions [ 31 , 32 ]; however, interestingly we did not observe a significant change in RMR in people following an intermittent fasting regimen, neither in healthy, normal-weight people [ 20 ] nor patients with type 2 diabetes [ 33 ]. Dietary interventions without reducing RMR are crucial, in particular with regard to weight regain following the intervention.…”
Section: Discussionmentioning
confidence: 87%
“…A decline in resting metabolic rate (RMR) is described for most caloric restriction interventions [ 31 , 32 ]; however, interestingly we did not observe a significant change in RMR in people following an intermittent fasting regimen, neither in healthy, normal-weight people [ 20 ] nor patients with type 2 diabetes [ 33 ]. Dietary interventions without reducing RMR are crucial, in particular with regard to weight regain following the intervention.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, larger RCTs should further explore the clinical effectiveness of fasting programs in metabolic syndrome patients [ 31 ]. In another study, Obermayer et al assessed the efficacy of IF in individuals with type 2 diabetes [ 32 ]. This study found that after 12 weeks of intervention, the IF group exhibited a significant reduction in total daily insulin dose of 9 ± 10 IU as opposed to the control group, with an increase of 4 ± 10 IU.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a CR murine model called meal feeding (MF) was established by feeding mice twice daily to reduce the fasting interval as a more appropriate reference for IF to distinguish CR from diet patterns. Every-other-day feeding (EODF) is the most commonly used research model for IF and has been applied in many clinical studies, even in individuals with diabetes, without serious adverse effects ( 17–21 ). Therefore, we used the MF model, where food intake was calculated based on the total consumption of the EODF group, distributed equally at 10:00 a.m. and 6:00 p.m. , effectively reducing the fasting duration to ∼12 h. This strategy guaranteed precise management of the intake variable and minimized extended fasting periods, which is a novel aspect of our experimental design.…”
Section: Introductionmentioning
confidence: 99%